I deserve more A’s: A report on the development of a measure of academic entitlement - Dennis L. Jackson; Marc P. Frey; Chelsea McLellan; Carolyn M. Rauti; Paige B. Lamborn; Jill A. Singleton-Jackson; Frantisek Sudzina (PLoS ONE, 2020)
This paper reports the results of a multi-stage effort to develop a measure of Academic Entitlement. An empirical/rational approach was taken to develop items and reduce the item set for a final version of the Academic Entitlement Scale (AES). The measure includes seven dimensions: Accommodation, Reward for Effort, Responsibility Avoidance, Grade Haggling, Customer Orientation, Customer Service Expectations, and General Academic Entitlement. Fit, using Confirmatory Factor Analysis, for the seven-factor correlated model and a bifactor model including General AE and the six specific factors, was good. The full measure is reported along with descriptive statistics for the scale and preliminary validation evidence.